The impact of conflict on the exchange rate of developing economies - Michail, Nektarios A. (My University, 2021)
This paper explores the impact different types of conflict have on the nominal exchange rate (NER), using a panel of developing economies. Accounting for NER determinants, the evidence suggests that in addition to the depreciation caused by macroeconomic factors, intra-state (civil) wars have a strong and significant depreciative impact on the exchange rate. In contrast, international wars do not appear to have any excess effect. A potential explanation of this phenomenon is that, unlike international wars where winners and losers are more difficult to distinguish a priori, in civil wars the country is much more likely to face economic deterioration, therefore promoting an over-discounting effect. The findings provide insights for both investors and policymakers given that exchange rate devaluation can likely provide a negative feedback mechanism to the local economy, especially if they hold foreign currency debt. The depreciation could also potentially have strong effects on the long-run growth potential, considering that most developing economies rely on imports of capital goods for research and development purposes.
Keywords: Civil war; Conflict; Developing economies; Nominal exchange rate; Shadow exchange rate